2021
DOI: 10.18805/ag.d-322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Five Mediterranean Shrubs Extracts on Larval Exsheathment of Haemonchus contortus

Abstract: Background: Mediterranean shrub species cover more than 70% of the total area in Tunisia and in summer when the herbaceous species have wilted, they constitute feeding resource for livestock. The use of tanniniferous shrubs seems to be a good alternative to control gastrointestinal nematodes infections in small ruminants. This study evaluated the in vitro anthelmintic (AH) effect of Ceratonia siliqua (C. siliqua), Periploca angustifolia Labill. (P. angustifolia) and Medicago arborea (M. arborea) against Haemon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another strategy recently explored is the use of natural compounds produced by edible mushrooms [ 53 , 54 ] and fungi with nematocidal activity [ 55 , 56 , 57 , 58 ], which, in the near future, are expected to replace, either fully or partially, chemically synthesized anthelmintic drugs routinely used in farms maintained under grazing systems. In recent years, other approaches, such as the use of bioactive plants for GIN control, have been widely explored [ 59 , 60 , 61 ]. Ethnoveterinary medicine is an ancient practice performed mostly by rural communities worldwide, which has emerged as a necessity to counteract anthelmintic resistance and the negative impacts of GIPN on animal welfare and performance [ 62 , 63 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy recently explored is the use of natural compounds produced by edible mushrooms [ 53 , 54 ] and fungi with nematocidal activity [ 55 , 56 , 57 , 58 ], which, in the near future, are expected to replace, either fully or partially, chemically synthesized anthelmintic drugs routinely used in farms maintained under grazing systems. In recent years, other approaches, such as the use of bioactive plants for GIN control, have been widely explored [ 59 , 60 , 61 ]. Ethnoveterinary medicine is an ancient practice performed mostly by rural communities worldwide, which has emerged as a necessity to counteract anthelmintic resistance and the negative impacts of GIPN on animal welfare and performance [ 62 , 63 ].…”
mentioning
confidence: 99%
“…The use of plants rich in these compounds as part of the diet for livestock under a nutraceutical approach could contribute to diminishing the parasite population in grazing animals [66,67]. Several studies, both in vitro and in vivo, have confirmed the use of PSM for GIPN control [60][61][62][63][64][65][66][67][68][69]. As the versatility of bioactive plants is one of their most appealing characteristics, they can be used as (i) a phytochemical source for drug development, (ii) as source of plant extracts or essential oils for animal drenching or (iii) as an addition to feedstuff with nutraceutical properties [70].…”
mentioning
confidence: 99%